Ending hunger: What would it cost? - Laborde Debucquet, David; Bizikova, Livia; Lallemant, Tess; Smaller, Carin (International Institute for Sustainable Development, 2016)
We are at a major turning point in history. For the first time ever the world has committed to ending hunger. Not to reduce or halve it—but to end hunger. When world leaders adopted the Sustainable Development Goals (SDGs) in September 2015, they agreed that this should be done by 2030. The International Institute for Sustainable Development (IISD) and the International Food Policy Research Institute (IFPRI) joined forces to estimate what it would cost to end hunger, and the contribution that donors need to make. We consider that a country has achieved this goal when the number of hungry people is less than 5 per cent of the population. This follows the approach used in the Millennium Development Goals (MDGs) and the Food and Agriculture Organization of the UN’s (FAO’s) State of Food Insecurity in the World (SOFI) report, which use the same threshold.